2001
DOI: 10.1590/s0101-81752001000500005
|View full text |Cite
|
Sign up to set email alerts
|

Fauna parasitária de peixes oriundos de "pesque-pague" do município de Franca, São Paulo, Brasil. I. Protozoários

Abstract: ABSTRACT. Parasitic fauna of cultivated fishes in feefishing farm ofFranca, São Paulo State, Brazil. I. Protozoans. The present work studied protozoan parasites of cultivated fishes (N = 433) from two feefishing fal111 situated in Franca, São Paulo, Brazil, during a period of April 1997 through March 1999. Specimens of piauçú Leporinus macrocephalus Garavello & Britski, 1988 (Anostomidae) o sistema de cultivo intensivo, usualmente praticado pelas pisciculturas industriais, caracteriza-se pelo aumento da densid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 9 publications
3
37
1
12
Order By: Relevance
“…However, the observed rates of infection were lower than those described for tambacu farmed in different regions other than the Brazilian Southeast (Tavares-Dias et al, 2001a;Schalch & Moraes, 2005), and were also lower than reports of P. mesopotamicus in the Central-West region (Sant'Ana et al, 2012), where this protozoan caused high mortality. Martins et al (2001) reported a mortality of 61.3% in the winter season (May-August) in the Southeast region, when water temperatures ranged from 17 to 24 o C. In the Central-West region, this protozoan occurred in winter and summer, and 100% of mortality was observed by Sant'Ana et al (2012).…”
Section: Resultscontrasting
confidence: 62%
See 4 more Smart Citations
“…However, the observed rates of infection were lower than those described for tambacu farmed in different regions other than the Brazilian Southeast (Tavares-Dias et al, 2001a;Schalch & Moraes, 2005), and were also lower than reports of P. mesopotamicus in the Central-West region (Sant'Ana et al, 2012), where this protozoan caused high mortality. Martins et al (2001) reported a mortality of 61.3% in the winter season (May-August) in the Southeast region, when water temperatures ranged from 17 to 24 o C. In the Central-West region, this protozoan occurred in winter and summer, and 100% of mortality was observed by Sant'Ana et al (2012).…”
Section: Resultscontrasting
confidence: 62%
“…The gastrointestinal tract was removed, placed in a Petri dish containing NaCl (0.8%), and examined under a stereomicroscope. The methods used for collection, fixation (Eiras et al, 2006;Thatcher, 2006), and quantification of the parasites (Tavares-Dias et al, 2001a, 2001b were performed according to previous recommendations. The identification of the collected parasites was done according to Díaz-Ungria (1968), Kritsky et al (1979), Thatcher & Paredes (1985), Boeger et al (2002), Belmont-Jégu et al (2004), andThatcher (2006).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations